MeSAUR1, Encoded by a Small Auxin-Up RNA Gene, Acts as a Transcription Regulator to Positively Regulate ADP-Glucose Pyrophosphorylase Small Subunit1a Gene in Cassava - Ma, Ping’an; Chen, Xin; Liu, Chen; Meng, Yuhong; Xia, Zhiqiang; Zeng, Changying; Lu, Cheng; Wang, Wenquan (Frontiers in Plant Science, 2017)
Cassava, being one of the top three tuberous crops, features highly efficient starch accumulation in the storage root to adapt the tropical resources and environments. The molecular mechanism for the process, however, is still unclear. ADP-glucose pyrophosphorylase, the first and rate-limited enzyme in starch biosynthesis pathway, is a heterotetramer comprised of two small/catalytic and two large/modulatory subunits. To understand the regulation of MeAGPase, the promoter of a highly expressed small subunit, MeAGPs1a, was used as bait for a yeast one-hybrid assay to screen storage root cDNA library. One cDNA, coding for a small auxin-up RNA protein, named MeSAUR1, was isolated from cassava. MeSAUR1 could bind to the promoter of MeAGPS1a in yeast one-hybrid test and in vitro, and was located in cell nucleus. MeSAUR1 displayed a higher transcript level in cassava root cortex, and its expression was induced by indole-3-acetic acid, gibberellin and ethylene, but repressed by abscisic acid. A dual-luciferase interaction test further convinced that MeSAUR1 could bind to the promoter of MeAGPS1a, and positively regulate the transcription of MeAGPS1a in cassava.